Preliminary study of neutron absorption by concrete with boron carbide addition - Abdullah Y.; Ariffin F.N.T.; Hamid R.; Yusof M.R.; Zali N.M.; Ahmad M.H.A.R.M.; Yazid H.; Ahmad S.; Mohamed A.A. (American Institute of Physics Inc., 2023)
Concrete has become a conventional material in construction of nuclear reactor due to its properties like safety and low cost. Boron carbide was added as additives in the concrete construction as it has a good neutron absorption property. The sample preparation for concrete was produced with different weight percent of boron carbide powder content. The neutron absorption rate of these samples was determined by using a fast neutron source of Americium-241/Be (Am-Be 241) and detection with a portable backscattering neutron detector. Concrete with 20 wt % of boron carbide shows the lowest count of neutron transmitted and this indicates the most neutrons have been absorbed by the concrete. Higher boron carbide content may affect the concrete strength and other properties. © 2014 AIP Publishing LLC.